PENERAPAN MODEL COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENINGKATKAN HASIL BELAJAR PESERTA DIDIK PADA KONSEP PERBANDINGAN - Dindin Koharudin (UJMES (Uninus Journal of Mathematics Education and Science), 2017)
The problem of mathematic learning at SMPN 2 Pacet are low of student’s learning outcome. The alternative learning model to enhance students is cooperative learning model of jigsaw type. This research measured the enhacement of students’ learning outcome. This research used classroom action research based on Hopkins model. The research has been conducted in two cycles, every cycle consist of planning step, action step, observing step, and reflection step.The population are students of class 8 F SMPN 2 Pacet. The instrument of data collection are observation sheets, post test (Essay questions), questioners and journal. The quantitative data came from posttest, however the qualitative data came from observation sheets, questioners and journals. The data analysis technic are used flow method including data reduction, data presentation and conclusion or verification. Based on analysis, analysis result showed that students outcome have enhanced/improved after the learning with cooperative learning model of jigsaw type.